Weed management in sugar cane : critical periods of weed competition and mechanisms of interference from Paspalum paniculatum and P. urvillei - Reinhardt, Carl Frederick (Charlie) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.